Exploring the Adoption of Metaverse Platforms in Corporations - Muhamad Irfan (Bright Publisher, 2024)
This study explored the adoption of metaverse platforms in Indonesian corporations through a moderated model integrating Self-Determination Theory and the Technology Acceptance Framework. Data were collected from 355 respondents through a structured questionnaire, of which 344 were deemed valid after a validation step confirming prior use of metaverse platforms. The research focused on understanding the factors influencing Usage Intention (UI) by examining the roles of Customization Capability (CUS), Immersive Experience Features (IMF), Social Influence (SOC), and Technology Reliability (TR) on Perceived Usefulness (PU). The results indicated that CUS, IMF, and TR significantly enhanced PU, which was a strong predictor of UI, underscoring the critical mediating role of perceived usefulness in driving adoption. The findings revealed that customization and reliability were pivotal in enhancing perceived utility, while the impact of immersive features, though positive, was less pronounced. SOC had a modest effect on UI, suggesting that direct functional benefits of the platform were prioritized by users over peer validation. The study contributed to the literature by providing an integrated model that highlights the importance of both individual and contextual factors in technology adoption within corporate environments. Practical implications suggest that corporations should focus on developing customizable, reliable, and functionally beneficial metaverse platforms to foster sustained adoption.